1993
DOI: 10.1159/000236399
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Various Beta-Lactam Antibiotic-Protein Conjugates and Cross-Reactivity of the Antibodies Produced in Guinea Pig

Abstract: Immunogenic properties of bovine serum albumin (BSA) conjugates of various β-lactam antibiotics (ABs) and cross-reactivity of the produced antibodies were investigated in guinea pigs. Each AB-BSA conjugate was immunized with complete Freund’s adjuvant. Following the second injection, AB-specific antibodies were detected with high titers. Produced antibodies showed concentration-dependent inhibition by the corresponding AB. Cross-reactivity between the produced antibodies and ABs was evaluated with two methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…These studies show very little cross reactivity between the b-lactam rings themselves (reaction to the b-lactam rings was one of the original explanations for the link between penicillin and cephalosporin allergies). More recent laboratory studies and several cohort studies confirm the role of the R1 side chain in the cross reactivity (11)(12)(13)(14)(15)(16)(17). Patients with an allergy to a specific cephalosporin also demonstrate cross reactivity to penicillin and other cephalosporins, as evidenced by an elevated immunoglobulin E (IgE) response when challenged (18).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies show very little cross reactivity between the b-lactam rings themselves (reaction to the b-lactam rings was one of the original explanations for the link between penicillin and cephalosporin allergies). More recent laboratory studies and several cohort studies confirm the role of the R1 side chain in the cross reactivity (11)(12)(13)(14)(15)(16)(17). Patients with an allergy to a specific cephalosporin also demonstrate cross reactivity to penicillin and other cephalosporins, as evidenced by an elevated immunoglobulin E (IgE) response when challenged (18).…”
Section: Resultsmentioning
confidence: 95%
“…However, similarities in the side chains does correlate with risk for cross reactivity (2,42). A number of studies indicate that the R1 side chain off the b-lactam ring rather than the ring itself is the determining factor for the rate of cross reactivity (8,9,11,(13)(14)(15)(16). In particular, the aminopenicillins, amoxicillin and ampicillin, have the same R-group side chains as several first-and secondgeneration cephalosporins (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with other published results, 8,15 indicating that penicillin conjugates with an intact b-lactam ring seem to have a generally low immunogenicity, whereas immunizations with penicilloyl protein conjugates result in high antibody titres. 19 Antipenicilloyl antibodies, however, are of little value for residue analysis, since they mainly react with the open ring form, while MRLs are set for the parent compounds. 1 Both mice producing specific antibodies against ampicillin were selected as the spleen donors for cell-fusions.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 39 , 40 , 41 Some studies showed that patients with hypersensitivity to particular cephalosporins could tolerate cephalosporins and suggested that the antibodies to the R-side chain rather than to the common BL ring are determining factors for the immune response to cephalosporins. 3 , 42 , 43 , 44 , 45 Furthermore, several clinical studies have found that cross-reactivity between penicillin and first and second generation cephalosporins with identical or similar side chains ranges from 14-38%. 1 , 43 , 46 , 47 In the present study, IgE ELISA inhibition results of cefaclor-HSA showed significant inhibitions with the addition of free cefaclor and minimal inhibitions with cephalexin (which shares an identical R-side chain with cefaclor).…”
Section: Discussionmentioning
confidence: 99%
“… 48 Although the role of IgG in anaphylaxis has not been elucidated in humans, it has been suggested that IgG-mediated anaphylaxis occurs in mice, and specific IgG to drugs may contribute to human anaphylaxis reactions to drugs. 45 In occupational allergic reactions, IgG antibody has been suggested to be associated with T helper2/B cells, induced IgE, and IgG4 production. 12 , 49 As a result of chronic antigen exposure, IgG4 antibodies are produced in humans.…”
Section: Discussionmentioning
confidence: 99%